GAMBARAN PENGETAHUAN DAN SIKAP PRIA PRODUKTIF TERHADAP METODE KONTRASEPSI VASEKTOMI - Ariyanto Ariyanto; Nurfitriani Nurfitriani (Jurnal Akademika Baiturrahim Jambi, 2018)
Vasectomy is an alternative method of contraception for men who do not want to have children anymore by undergoing minor surgery to stop male reproductive capacity. The method of this research is quantitative analytical with cross sectional design, sample number of KK 50 samples, sampling using puporsive sampling. Data collection techniques using questionnaires, univariate data analysis. The results showed that the knowledge was 100% did not know the social factors that influence the selection of contraception, 11 respondents (22.0%) did not know what advantage in choosing the method of vasectomy contraception, 18% do not know how many children are allowed to use vasectomy contraception and 16.0 % who do not know the age of husbands who may use vasectomy contraception, productive man attitude there are 36.0% hesitated that vasectomy contraception is a safe and effective birth control for couples of childbearing age, 44.0% hesitant to use vasectomy contraception did not affect subsequent sexual relations, 90.0%  hesitant to use vasectomy contraception is not against religion,  60,0% hesitate contraception vase ktomi may reduce the desire for sexual intercourse (libido), 56.0% doubt the use of vasectomy does not result in men become impotent (not male), and 56.0% hesitant men who became vasectomy acceptors can ejaculate (semen discharge).